A Literature Review Child abuse and Neglect: Potential Impact on Children during A Covid-19 Pandemic - Endang Mei Yunalia; Arif Nurma Etika; Satria Eureka Nurseskasatmata; Wiwin Sulistyawati (Journal for Quality in Public Health, 2020)
Background: Staying at home during Covid-19 pandemic is no longer a safety aspect. During lockdown there is clustering of all the family members at home. Parents or caregivers must manage their children’s schooling as well as their own work and parenting responsibilities. Some articles mention that Covid-19 pandemic turning into “broader child crisis” such as violence against on children. Child abuse can take place in a home environment under the care of parents or other family members. Purpose: Analyze the impact of isolation policies caused the spread of COVID-19 and evidence of child abuse during Covid-19 pandemic Methods: This literature review is arranged based on literatures studies from 5 databases last 6 years, such as DOAJ, Google Scholar, ResearchGate, SpringerLink, and Elsevier Open Access Journals. This literature review searched for studies with the keyword “child abuse” or “child neglected” or “covid-19 pandemic impact”. Based on a search using these keywords, 8 articles were found from the data base. Results: Building awareness about child abuse and neglect during Covid-19 pandemic is vital, because children are often vulnerable and require careful consideration by parents or caregivers and health care system. So, to protecting children from violence during Covid-19 pandemic requires all sectors to undertake coordinate measure (parents or caregiver, school, community and health profession). Conclusion: The health profession has a duty to provide support with public health approach in overcoming about child abuse and neglect.